Left ventricular dysfunction in preeclampsia: an echocardiographic study - Sengodan, Subha Sivagami; Dhanapal, Mohana; Pandian, Anbarasi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Preeclampsia is a pregnancy specific disorder which constitutes hypertension and proteinuria after 20 weeks of gestation. It is a multisystem disorder of unknown etiology. Preeclampsia is associated with significantly higher prevalence of asymptomatic global left ventricular function and myocardial injury than uneventful pregnancy. This study was undertaken to evaluate the Left ventricular changes in preeclamptic women and to compare with normotensive women. Methods: This prospective study on left ventricular systolic and diastolic function by echocardiography was undertaken in normal and preeclamptic pregnant women who got admitted during the period of one year from January 2015 to December 2015 at Government Mohan Kumaramangalam Medical College and Hospital, Salem. Study population was divided into two groups. GROUP 1-Preeclamptic pregnant women GROUP 2-Normotensive pregnant women as control. Results: There were significant differences in the mean end diastolic dimensions when compared to systolic dimension between two groups. Conclusions: Women with preeclampsia have significant systolic and diastolic dysfunction compared to normotensive pregnant women. Effective management of patients who showed left ventricular dysfunction prevented pulmonaryedema and cardiac failure. This study emphasizes the importance of identifying this subset of preeclamptic patients with ECHO changes who are at higher risk of developing cardiovascular complications later in life by undergoing echocardiography.